2020
DOI: 10.1186/s12902-020-00604-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social determinants, diabetes knowledge, health behaviors, and glycemic control in type 2 diabetes: an analysis from real-world evidence

Abstract: Background: Although important achievements have been done in type 2 diabetes mellitus (T2D) treatment and glycemic control, new strategies may take advantage of non-pharmacological approaches and of other potential determinants of health (e.g., socioeconomic status, education, diabetes knowledge, physical activity, and self-care behavior). However, the relationships between these factors are not totally clear and have not been studied in the context of large urban settings. This study aimed to explore the rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Human health outcomes are unequally distributed throughout populations [ 1 ]. Due to differences among population groups subdivided according to age and other demographic characteristics over time, there is a need for epidemiological studies to evaluate observed trends, plan for health care services, and launch interventions to improve health [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human health outcomes are unequally distributed throughout populations [ 1 ]. Due to differences among population groups subdivided according to age and other demographic characteristics over time, there is a need for epidemiological studies to evaluate observed trends, plan for health care services, and launch interventions to improve health [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been a growing awareness of the inequality of social determinants of health (SDOH) leading to health disparities and poor DM control. Silva-Tinoco et al conducted a multicenter cross-sectional study in patients with type 2 diabetes (T2D) from 28 primary care outpatient centers located in Mexico City and found that socioeconomic and educational gradients influence diabetes knowledge among primary care patients with type 2 diabetes [ 15 ]. Education and socioeconomic status are not the only SDOHs affecting DM care.…”
Section: Discussionmentioning
confidence: 99%
“…Disparities in dilated eye examinations, low-density lipoprotein (LDL) testing, HbA1c control, blood pressure management, and statin treatment have been documented in insured contexts. A study of 21 VA hospitals encountered that Blacks with diabetes were better likely than Whites to be treated in lower-performing establishments, which may explain a few of the racial disparities in diabetes quality standards [ 34 ].…”
Section: Reviewmentioning
confidence: 99%